First record of red lobster (Panulirus penicillatus) in Ecuadorian continental shore - Figueroa-Guzmán, Jorge (2024)
Panulirus penicillatus is a lobster species primarily found in insular regions but also recorded in coastal continental zones of various countries along the American Pacific. This study reports P. penicillatus for the first time in the coastal area of Manabí Province, mainland Ecuador. Previously, its presence was known only in the Galápagos Islands, where it is a commercial species. The record is based on two adult individuals of P. penicillatus, both collected in October 2023 from fishing activities, one through nighttime apnea diving and the other via artisanal fishing using a gillnet.